Grain Boundary Segregation: the New Sprouts - Bokstein, Boris; Itckovich, Alexei; Pokhvisnev, Yury; Rodin, Alexei (Diffusion Fundamentals, 2022)
Some aspects of grain boundary segregation (GBS) are discussed. This paper adds two new sprouts. The first is connected with formation of the atomic complexes in boundary region and their effect on grain boundary diffusion (GBD). The second – with a nonhomogeneity of energy distribution between boundary sites.